PROFESIONALISME GURU DALAM PERSPEKTIF ISLAM - Yanti, Nova (STAI Hubbulwathan Duri, 2017)
The various of regulations and legislation about teachers is part of the long-term effort and strategy to improve the quality of education.The experts generally agree that the improvement of the quality of education stems from the improvement of the quality of the teachers. Beside has the knowledge and skill, the power of thinking, an ulil albab alsomust have moral value, obligation and responsibility to built a civilization. When a scholar is defined as someone who has a deep religious knowledge, very high moral and has a responsibility to educate public. It is not wrong, even though it is not enough. Ulama in the classical period of Islam was according to the guidance of Al-Qur’an are those who not only master the science of religion but the general science and responsible for building civilization.